2001
DOI: 10.1007/s002590100647
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of myocardial ischaemia in the emergency department by rest or exercise 99mTc tracer myocardial SPET in patients with chest pain and non-diagnostic ECG

Abstract: Chest pain (CP) represents a frequent reason for presentation at the emergency department (ED). A large proportion of patients have non-diagnostic ECG on presentation, and in many cases several hours have elapsed since onset of symptoms. Acute rest myocardial scintigraphy (rest SPET) has been shown to have a relevant role in the detection of patients at risk for coronary events, but its sensitivity and negative predictive value are optimal only within the first 3 h following onset of symptoms. In those with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…c Statistically significant negative correlation with the SYNTAX score (P < 0.001). [21][22][23]. Our findings showed that R-GSPECT and S-GSPECT had high sensitivity, specificity, NPV, PPV, and accuracy for the diagnosis of ACS in the low-intermediate risk group, in agreement with the existing literature.…”
Section: Discussionsupporting
confidence: 93%
“…c Statistically significant negative correlation with the SYNTAX score (P < 0.001). [21][22][23]. Our findings showed that R-GSPECT and S-GSPECT had high sensitivity, specificity, NPV, PPV, and accuracy for the diagnosis of ACS in the low-intermediate risk group, in agreement with the existing literature.…”
Section: Discussionsupporting
confidence: 93%
“…[21][22][23][24][25] The addition of stress imaging in stable patients improves diagnostic accuracy. 26 Although very useful for assessment of ischemic burden and planning future management, a normal SPECT does not exclude the presence of significant coronary disease. Balanced ischemia due to disease of all 3 major coronary arteries or the left main coronary artery may obscure qualitative detection of reduced perfusion, whereas attenuation artifacts may produce false-positive results.…”
Section: Testing Optionsmentioning
confidence: 99%
“…54 However, according to current guidelines, most CPU order stress SPECT if serial 12-lead ECG and cardiac biomarker measurements are normal, which has been shown to improve diagnostic accuracy. 34,55 Conversion of nondiagnostic exercise studies (achieve Ͻ85% of maximal heart rate) to pharmacological stress (eg, adenosine) is recommended. A drawback to rest-stress SPECT studies is radiation exposure, which is estimated to average 11.3 mSv with sestamibi and 9.3 mSv with tetrofosmin and is greater than the exposure from most diagnostic invasive angiograms (average, 5 to 7 mSv).…”
Section: Current Standard Diagnostic Testingmentioning
confidence: 99%